Role of technology forecasts for planning of science, technology and innovation strategies - Hoa, Nguyen Viet (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Planning science, technology and innovation strategies (abbreviation of strategic planning) in a new context that promotes engagement with science, technology and innovation forecasts. The forecast provides scientific foundation based on scientific methodology, reflects honestly and objectively on the movement and development of science, technology and innovation and the trend of science, technology and innovation will develop in the future. As a result, the highly valuable product of the forecast is to model, scenerio or provide information and data to create a picture of the development trend of science, technology and innovation in the future for strategic planners to choose the most optimal model or scenario into the strategy. The scope of research on strategic planning and forecasting of science, technology and innovation is very wide, but this article will limit and focuse on three main contents: (i) Reasoning the role of technology forecasts with strategic planning; (ii) Methodology of technology forecasting for strategic planning; (iii) Some of the issues that are suggestive for Vietnam. Code: 18070101